ESSENTIAL OILS AS NATURAL FOOD ADDITIVES: STABILITY AND SAFETY - Frederico, Camila; Franciscato, Lidaiane Mariáh Silva dos Santos; Pereira Ruiz, Suelen (Arquivos de Ciências da Saúde da UNIPAR, 2023)
Essential oils are volatile aromatic liquids derived from the secondary metabolism of plants, consisting of a complex mixture of different active compounds. Several medicinal plants are sources for the extraction of essential oils, being recognized as safe (GRAS) by the FDA (Food and Drug administration). The use of essential oils as possible food preservatives has been gaining ground in research due to their antioxidant and antibacterial activities, important characteristics in food preservation and also to the population's interest in consuming healthier products. Essential oils are a promising alternative for the food industry, as they act to control pathogenic and deteriorating bacteria. Compared to synthetic chemical preservatives, essential oils are generally safer, but have low stability, so encapsulation is a way to protect them from adversities. This review aims to demonstrate the effectiveness, stability and safety of essential oils and their use in food matrices.